Selected plant essential oils and their main active components, a promising approach to inhibit aflatoxigenic fungi and aflatoxin production in food. Issue 8 (3rd August 2018) - Gómez, José Vicente; Tarazona, Andrea; Mateo-Castro, Rufino; Gimeno-Adelantado, José Vicente; Jiménez, Misericordia; Mateo, Eva M.
ABSTRACT: Recent research has showed that Aspergillus flavus and Aspergillus parasiticus are aflatoxigenic species that can become very competitive in the framework of climate change. Aflatoxins show carcinogenic, mutagenic, immunotoxic and teratogenic effects on human and animals. Effective and sustainable measures to inhibit these species and aflatoxins in food are required. Origanum vulgare and Cinnamomum zeylanicum essential oils (EOs) and their major active constituents, carvacrol and cinnamaldehyde, respectively, were assayed for inhibiting these species and aflatoxin production in maize extract medium under different environmental conditions. Doses of 10–1000 mg l −1 were assayed and the effective doses for 50 (ED50 ) and 90% (ED90 ) growth inhibition were determined. The ED50 of cinnamaldehyde, carvacrol, oregano EO, and cinnamon EO against A. flavus were in the ranges 49–52.6, 98–145, 152–505, 295–560 mg l −1 and against A. parasiticus in the ranges 46–55.5, 101–175, 260–425 and 490–675 mg l −1, respectively, depending on environmental conditions. In A. flavus treatments ED90 were in the ranges 89.7–90.5, 770–860 and 820–>1000 mg l −1 for cinnamaldehyde, carvacrol and cinnamon EO, and in A. parasiticus treatments in the ranges 89–91, 855–>1000 and 900–>1000 mg l −1, respectively. ED90 values for oregano EO against both species were >1000 mg l −1 . Growth rates of both species were higher at 37 than at 25°C and at 0.99 than at 0.96 aw . Aflatoxin production was higher at 25 than at 37°C. Stimulation of aflatoxin production was observed at low doses except for cinnamaldehyde treatments. The effectiveness of EOs and their main constituents to inhibit fungal growth and aflatoxin production in contact assays was lower than in vapour phase assays using bioactive EVOH-EO films previously reported.